“Sepuh” in puppetry tradition of wayang kulit performance in ruwatan ceremony - Efendi, Agus; Harsono, Harsono; Deswijaya, Adi; Pardyatmoko , Pardyatmoko (Gelar: Jurnal Seni Budaya, 2024)
Ruwatan is a self-cleansing method in Javanese society for those considered sukerta (spiritually unclean person). To prevent a misfortune in life, the sukerta people must be ritually cleaned. The Murwakala performance is led by a dhalang ruwat in this ruwatan ceremonial procession, therefore a dhalang plays an important role. However, several qualifications must be met before being ordained as a dhalang ruwat and trusted to lead the ruwatan sukerta procession. The objective of the study is to explore the concept of old-aged (sepuh) in becoming a dhalang ruwat. The descriptive qualitative model was used to develop this study, the results of which were descriptions of field notes in the form of interviews with dhalang ruwat, observations, and documentation. The results showed that in order to become a dhalang ruwat, one must be descended from a dhalang ruwat, be a role model, and have married their offspring. The notion of sepuh (old-aged) in becoming a dhalang ruwat includes being psychologically mature in terms of age, as well as being spiritually capable in terms of social position.